Exponential Growth and New Agendas – a Comprehensive Review of the Arctic Conference Sphere - Steinveg, Beate (Arctic Review on Law and Politics, 2021)
The Arctic region has attracted the interest of Arctic and non-Arctic states, as well as non-state actors, for decades. Corresponding with the growing attraction towards the region, the number of conferences attending to Arctic issues has expanded. This article provides an historical mapping of the Arctic conference sphere, and demonstrates how the establishment of Arctic conferences has both paralleled central events in Arctic affairs and can be linked to important international developments. Firstly, there is a notable peak conforming with the “second state change” in 2005, brought about by developments opening the Arctic to global concerns: the impacts of climate change and the spread of the socio-economic effects from globalization to the Arctic. Secondly, the expanding number of conferences around 2013 can be seen in relation to the growing interest in the region from non-Arctic states. As such, this article builds the argument for conferences as a central element within the Arctic governance architecture, creating linkages among units in the regime complex. The article devotes particular attention towards the two largest international conferences on Arctic issues – Arctic Frontiers and Arctic Circle Assembly – to illustrate how the necessity for hybrid policy-science-business conferences arose from a more complex governance system, and challenges requiring cross-sectoral, interdisciplinary, and international collaboration.